The Elmo family forms an ancient group of actin-regulating proteins - Joseph A. Brzostowski; Petra Fey; Jianshe Yan; Nilgun Isik; Tian Jin (Communicative & Integrative Biology, 2009)
The Elmo protein family members are important mediators of small G protein activity, regulating actin-mediated processes such as chemotaxis and engulfment.  Until recently,1 Elmo function has not been explored in professional phagocytes such as Dictyostelium discoideum. We discuss the significance of this family with respect to pathways that regulate Rac signaling, we present a comparison of Elmo proteins between representative taxa, and discuss our findings on ElmoA, one of six Elmo proteins found in D. discoideum.